THE SIGNIFICANCE OF MICROCHOLECYSTOSTOMY UNDER ULTRASOUND GUIDED IN THE TREATMENT OF PATIENTS WITH ACUTE CHOLECYSTITIS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
A review of the literature is presented, revealing the clinical features of complicated forms of gallstone disease, the essence of the problem of acute destructive cholecystitis and the high therapeutic and diagnostic effectiveness of diapeutic decompression techniques. It was noted that there is no consensus on the indications for use and the method of minimally invasive decompression intervention for acute cholecystitis in patients with high operational and anesthetic risk.